Molecular Approaches in Plant Abiotic Stress - Gaur, Rajarshi Kumar; Sharma, Pradeep K., 1953- (CRC Press, 2014)
Plants under abiotic stress are those suffering from drought, extreme temperatures, flood and other natural-but non-living-factors. Abiotic stress is responsible for reduced yields in several major crops, and climate change is focusing research in this area. To minimize cellular damage cause by such stresses, plants have evolved complex, well-coordinated adaptive responses that operate at the transcriptional level. Understanding these processes is key to manipulating plant performance to withstand stress. This book deals with the role of gene silencing in the adaptation of plants to these s.